Characterization of the Pathology, Biochemistry, and Immune Response in Kunming (KM) Mice Following Fasciola gigantica Infection - Mei, Xuefang; Zhang, Yaoyao; Quan, Chenyu; Liang, Yiying; Huang, Weiyi; Shi, Wei (Frontiers in Cellular and Infection Microbiology, 2022)
As a putative model of Fasciola gigantica infection, detailed data in Kunming (KM) mice infected with F. gigantica are lacking. In this study, KM mice were orally infected with 15 metacercaria for 8 weeks. Macroscopic and microscopic changes, serum biochemistry, cytokine responses, and changes in parasite-specific IgG antibody levels were monitored at 1, 3, 5, 7, and 8 weeks post-infection (wpi), respectively. The serum levels of AST and ALT increased after infection, while that of ALB decreased, which was positively correlated with the degree of liver damage. Between the fifth- and seventh-wpi, the mice showed symptoms of anemia and weight loss, possibly caused by the decrease of ALP. Moreover, the changing tendencies of GLB level and parasite-specific IgG antibody level were similar, suggesting a potential correlation between GLB production and adaptive immune response in the host. Coordinated variation of IFN-γ and IL-4 indicated a mixed Th1/Th2 cellular immune response. Furthermore, the serum IgG antibody increased after infection and peaked at 5 wpi, and was positively correlated with average parasite burdens. The worms collected from the mice were approximately 1 cm in length at 8 wpi, the digestive system and reproductive system of the worms were well developed, and no eggs were found in the uterus. To the best of our knowledge, it is the first report to describe detailed histological, biochemical and immunological indices in KM mice infected by F. gigantica, which provides the basic information of KM mice against the infection of F. gigantica.